Date Fruit and Seed in Nutricosmetics - Khlood Lafi Alharbi; Jegadeesh Raman; Hyun-Jae Shin (Cosmetics, 2021)
Many recent studies in the field of cosmetics have focused on organically sourced substances. Products made from organic materials are safe, high quality, cruelty-free, and more effective than those made from synthetic materials. Many organic compounds are known to be physiologically active in humans and have an extended storage capacity and long-lasting environmental effects. Agro-industrial waste has recently increased substantially, and the disposal of date palm waste, often performed in primitive ways such as burning, is harmful to the environment. Fruit processing industries generate over 10% of the total date seed waste daily, which could be converted into useful food products. Date fruit and seed are rich in sugar, vitamins, fiber, minerals, and phenolic compounds with antioxidant and anti-inflammatory properties that significantly promote human and animal health. This waste is rich in bioactive compounds and essential oils used in many kinds of food, medicine, and cosmetics. Most active cosmetic ingredients come from natural sources such as fruit, fish, and dairy, and recent research shows that date extract and seed oil help to reduce melanin, eczema, acne, and dry patches, while increasing skin moisture and elasticity. This review details the bioactive compounds and nutraceutical properties of date fruit and seed, and their use as cosmetic ingredients.